ULUMUL QUR’AN - Tasya Amanda; Suci Julianti; Qonita Syukro (Jurnal Kajian Islam dan Sosial Keagamaan, 2023)
The Al-Qur'an is the holy book of Muslims which was revealed to the Prophet Muhammad Sallallahu 'Alaihi Wa Sallam through the angel Gabriel. The Qur'an contains the words of Allah Subhanahu Wa Ta'ala which are a guide to life for mankind. While Ulmul Qur'an is: Science which includes discussions related to the Qur'an from the aspects of asbab al-nuzul, codification and orderly writing of the Qur'an, verses revealed in Mecca and verses revealed in Medina and other aspects related to the Koran. The concept of education according to the Koran is very clear. There are various verses that explain education. In reviewing this paper, we used library research methods by critically and in-depth studying library materials that are relevant to the paper material, such as books and journals that are suitable as references. As stated by Miqzaqon T and Purwoko, library research is a study used to collect information and data with the help of various kinds of materials in libraries such as documents, books, magazines, historical stories and so on. The aim of studying the Ulumul Qur'an is to protect Muslims from possible attempts to obscure the Qur'an by people who do not believe in or even deny the Qur'an. The Koran functions as a guide to life for Muslims. Moreover, it is also a primary source of law. which covers everything. The science of the Qur'an has developed and been carried out since the collection of the Qur'an during the time of the Prophet Muhammad and his companions until research on the science of the Qur'an today. There are many scholars who developed the knowledge of the Koran and many other books written by famous travelers.